Barriers to accessing health services during the COVID-19 pandemic in Poland: A nationwide cross-sectional survey among 109,928 adults in Poland - Paulina Mularczyk-Tomczewska; Adam Zarnowski; Mariusz Gujski; Mateusz Jankowski; Iwona Bojar; Artur Wdowiak; Jan Krakowiak (Frontiers Media S.A., 2022)
IntroductionThe COVID-19 pandemic has significant socio-economic implications for numerous industries, including healthcare. Disruptions of essential health services were reported by nearly all countries around the world. A detailed assessment of the healthcare uptake is necessary to estimate the potential health effects of the COVID-19 pandemic on the population. This study aimed to assess the prevalence of barriers to accessing health services during the COVID-19 pandemic in Poland as well as to identify factors associated with the disturbed access to healthcare during the pandemic.MethodsThis cross-sectional survey was carried out among Internet users in Poland using the computer-assisted web interview technique. Data were collected between October and December 2021. The questionnaire included 32 questions on sociodemographic characteristics, the COVID-19 pandemic, health status, daily habits as well as the use of healthcare during the COVID-19 pandemic.ResultsData were obtained from 102928 adults, the mean age was 48.0 ± 14.2 years, and 57.2% were females. Most of the respondents had visited a doctor during the past 12 months (70.4%). Almost half of adults in Poland (49.7%) reported barriers to access health services in the past 12 months. Out of 51,105 respondents who had experienced barriers to accessing health services during the COVID-19 pandemic, only 54.3% had visited a doctor in the past 12 months. Long waiting time (39.5%) and temporary closure of healthcare facilities/transformation into a COVID-19 dedicated center (28.8%) were the most common barriers indicated by the respondents. In multivariable logistic regression, female gender, age 18-49 years, lack of higher education, living in cities between 51,000 and 200,000 residents or above 500,000 residents, and having at least one chronic disease were significantly (p < 0.05) associated with higher odds of experiencing barriers to accessing health services during the COVID-19 pandemic.ConclusionsThis study confirmed that the COVID-19 pandemic has worsened access to health services in Poland. During the pandemic, new barriers to accessing health services, such as the temporary closure of healthcare facilities for non-COVID patients were revealed. Findings from this study provided patients' perspectives on barriers to accessing health services in Poland that may be used by policymakers to reduce health inequalities.